pH effects on the molecular structure of β-lactoglobulin modified air-water interfaces and its impact on foam rheology - Peukert, Wolfgang; Engelhardt, Kathrin; Konnerth, Christoph-Günther; Braunschweig, Björn; Lexis, Meike; Gochev, Georgi; Miller, Reinhardt; Willenbacher, Norbert (Langmuir, 2013)
Macroscopic properties of aqueous β-lactoglobulin (BLG) foams and the molecular properties of BLG modified air-water interfaces as their major structural element were investigated with a unique combination of foam rheology measurements and interfacial sensitive methods such as sum-frequency generation and interfacial dilatational rheology. The molecular structure and protein-protein interactions at the air-water interface can be changed substantially with the solution pH and result in major changes in interfacial dilational and foam rheology. At a pH near the interfacial isoelectric point BLG molecules carry zero net charge and disordered multilayers with the highest interfacial dilatational elasticity are formed at the air-water interface. Increasing or decreasing the pH with respect to the isoelectric point leads to the formation of a BLG monolayer with repulsive electrostatic interactions among the adsorbed molecules which decrease the interfacial dilational elasticity. The latter molecular information does explain the behavior of BLG foams in our rheological studies, where in fact the highest apparent yield stresses and storage moduli are established with foams from electrolyte solutions with a pH close to the isoelectric point of BLG. At this pH the gas bubbles of the foam are stabilized by BLG multilayers with attractive intermolecular interactions at the ubiquitous air-water interfaces, while BLG layers with repulsive interactions decrease the apparent yield stress and storage moduli as stabilization of gas bubbles with a monolayer of BLG is less effective. © 2013 American Chemical Societ
Keywords: interface; surface; multilayer; foam; charge; bubble; stabilization